ASSESSING SPEAKING SKILLS (Ustozlar uchun, 2025)
This paper explores the key principles, methods, and challenges involved in assessing speaking skills in English language learning. Speaking is a productive skill that reflects a learner’s ability to communicate effectively and spontaneously in real-life contexts. Accurate assessment of speaking skills requires considering fluency, pronunciation, accuracy, vocabulary, and interactional competence. The study discusses both traditional and modern assessment approaches, such as oral interviews, presentations, and computer-assisted testing. It also emphasizes the importance of reliable scoring rubrics, examiner training, and the use of technology to ensure fairness and validity. The paper concludes that effective speaking assessment should integrate communicative performance with practical evaluation techniques.